A DEEP SEISMIC INVESTIGATION OF THE FLEMISH CAP MARGIN: IMPLICATIONS FOR THE ORIGIN OF DEEP REFLECTIVITY AND EVIDENCE FOR ASYMMETRIC BREAK-UP BETWEEN NEWFOUNDLAND AND IBERIA - Hopper J.R.; Funck T.; Larsen H.C.; Tucholke B.E.; Louden K.E.; Holbrook W.S. (My University, 2006)
Seismic reflection and refraction data were acquired along the southeast margin of Flemish Cap at a position conjugate to drilling and geophysical surveys across the Galicia Bank margin. The data document first-order asymmetry during final break-up between Newfoundland and Iberia. An abrupt necking profile of continental crust observed off Flemish Cap contrasts strongly with gradual tapering on the conjugate margin. There is no evidence beneath Flemish Cap for a final phase of continental extension that resulted in thin continental crust underlain by a strong 'S'-like reflection, which indicates that this mode of extension occurred only on the Galicia Bank margin. Compelling evidence for a broad zone of exhumed mantle or for peridotite ridges is also lacking along the Flemish Cap margin. Instead, anomalously thin, 3-4-km-thick oceanic crust is observed. This crust is highly tectonized and broken up by high-angle normal faulting. The thin crust and rift structures that resemble the abandoned spreading centre in the Labrador sea suggest that initial seafloor spreading was affected by processes observed in present-day ultra-slow spreading environments. Landwards, Flemish Cap is underlain by a highly reflective lower crust. The reflectivity most likely originates from older Palaeozoic orogenic structures that are unrelated to extension and break-up tectonics. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CONTINENTAL BREAKUP; NEWFOUNDLAND MARGIN; RIFTING